ANALISA BUFFER DALAM SISTEM INFORMASI GEOGRAFIS UNTUK PERENCANAAN RUANG KAWASAN - Aqli, Wafirul (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT On the scale of area or region in spatial planning, it is important to evaluate and to predict the new spatial plan and policy, whether it is effective or not to be implemented. It is intended that the results of the spatial planning in scale of area or region, can be optimized to accommodate the needs. Geographical Information System as a computerized instrument of planning is pretty decent to be used for those stages of planning (evaluation and prediction). More specifically one of its analysis feature, buffer analysis, is capable to measure the effectiveness of the presence of public facilities –for example- in terms of coverage/distribution of services (in the context of evaluation stage). In addition, buffer analysis also capable to predict whether the spatial policies and its physical implementation possible to be place in accordance with the goal of the planning. Keyword: Geographical Information System, Buffer Analysis, Spatial Planning.